Renewable energies and the limits of development cooperation. A critical analysis based on the Global Covenant of Mayors for Climate and Energy Support Programme - Arredondo Chopitea, Ander (Revista Española de Desarrollo y Cooperación, 2021)
This article critically examines the connections and limits between the development of capitalism in nature, the procurement, use and transfer of renewable energy resources, and development cooperation. Cheap energy is essential to ensure the processes of capital accumulation, so that international environmental and development cooperation agreements prioritise the reproduction of the system over ecological needs. This is reflected in development cooperation instruments and actions to promote renewable energies, as in the case of the Programme of Support for the Global Covenant of Mayors for Climate and Energy.
Keywords: Development cooperation; Sustainable Development Goals; Renewable energies; Global Covenant of Mayors for Climate & Energy; Capitalocene